Combined immune checkpoint blockade (anti-PD-1/anti-CTLA-4): Evaluation and management of adverse drug reactions - Hassel, Jessica C.; Heinzerling, Lucie; Aberle, Jens; Baehr, Oliver; Eigentler, Thomas K.; Grimm, Marc-Oliver; Gruenwald, Victor; Leipe, Jan; Reinmuth, Niels; Tietze, Julia K.; Trojan, Joerg; Zimmer, Lisa; et al. (Cancer Treatment Reviews, 2017)
BACKGROUND: Combined immune checkpoint blockade (ICB) provides unprecedented efficacy gains in numerous cancer indications, with PD-1 inhibitor nivolumab plus CTLA-4 inhibitor ipilimumab in advanced melanoma as first-ever approved therapies for combined ICB. However, gains in efficacy must be balanced against a higher frequency and severity of adverse drug reactions (ADR). Because delays in diagnosis and management might result in symptom worsening and further complications, clinicians shall be well trained to identify ADR promptly and monitor patients adequately. This paper reviews safety data assessed by the European Medicines Agency for the anti-PD-1/CTLA-4 combination and provides a literature overview on published case reports for rare ADR with suspected potential underreporting. Incidences and kinetics of immune-related ADR are described. Recommendations for the evaluation and management of ADR are convened by an interdisciplinary expert panel focusing on rare but clinically important side effects arising from combined ICB. Pooled safety data from 1551 patients with advanced melanoma, treated either with 3mg/kg ipilimumab plus 1mg/kg nivolumab (N=407), or nivolumab alone (N=787), or ipilimumab alone (N=357) demonstrate that immune-related ADR occur more frequently for the combination, with a shorter time-to-onset, and tend to be more severe. The majority of events is reversible after systemic use of glucocorticoids, notably methylprednisolone or equivalents; in certain cases of long-lasting and refractory immune toxicities, non-steroidal immunosuppressants may be used, once ICB is interrupted or terminated. Combined ICB has considerable toxicities, therefore close monitoring and high experience in diagnosis and treatment of ADR is necessary.
EVALuna2:34333